2019
DOI: 10.7554/elife.43290
|View full text |Cite
|
Sign up to set email alerts
|

The impact of measles immunization campaigns in India using a nationally representative sample of 27,000 child deaths

Abstract: India comprises much of the persisting global childhood measles mortality. India implemented a mass second-dose measles immunization campaign in 2010. We used interrupted time series and multilevel regression to quantify the campaign’s impact on measles mortality using the nationally representative Million Death Study (including 27,000 child deaths in 1.3 million households surveyed from 2005 to 2013). 1–59 month measles mortality rates fell more in the campaign states following launch (27%) versus non-campaig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…We identified pneumonia deaths from the MDS using ICD-10 codes A37, H65-H68, H70, H71, J00-J22, J32, J36, J85, J86, P23, and U04, and diarrhea deaths as codes A00 and A02-A09. We excluded 272 deaths from our pneumonia case definition and 132 child deaths from our diarrhea case definition which had a reported history of measles by the VA respondent, in an effort to minimize misclassification of deaths which may be secondary to a measles infection (Wong et al, 2019). We excluded an additional 557 child deaths due to typhoid or paratyphoid fever (ICD-10 code A01) from our diarrhea case definition, as these cases do not share a common symptom profile with other infectious causes of diarrheal disease (Morris et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified pneumonia deaths from the MDS using ICD-10 codes A37, H65-H68, H70, H71, J00-J22, J32, J36, J85, J86, P23, and U04, and diarrhea deaths as codes A00 and A02-A09. We excluded 272 deaths from our pneumonia case definition and 132 child deaths from our diarrhea case definition which had a reported history of measles by the VA respondent, in an effort to minimize misclassification of deaths which may be secondary to a measles infection (Wong et al, 2019). We excluded an additional 557 child deaths due to typhoid or paratyphoid fever (ICD-10 code A01) from our diarrhea case definition, as these cases do not share a common symptom profile with other infectious causes of diarrheal disease (Morris et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Mortality among children aged 5–14 years is less well studied and recent estimates suggest a combined burden of almost 30,000 pneumonia and diarrhea deaths in India in 2016 (Fadel et al, 2019). The declines in pneumonia and diarrhea mortality during the last decade or so have mostly been driven by expanding treatment, improved nutrition, and vaccination against measles and standard childhood antigens (Bhutta et al, 2013; Wong et al, 2019). Newer vaccines such as rotavirus and pneumococcal conjugate vaccines have been only recently added to India’s Universal Immunization Program (Arora and Swaminathan, 2016; Sachdeva, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The government of India introduced the MCV2 in 2010 among all the states and union territories in various phases. Surveillance-based studies in different areas in India have demonstrated positive correlations with optimal MCV2 vaccination and reduced rates of measles-related mortality [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Following the successful implementation of the 2017 measles and rubella campaigns the confirmed measles cases in India dropped to 10,695. Earlier measles vaccination campaigns in India, such as the 2010 two dose measles campaign are estimated to have saved the lives of 41,000–56,000 children between 2010 and 2013 — equivalent to 39–57% of the expected number of measles deaths nationwide [ 26 ]. Despite the remarkable progress in measles control, India still has the fourth highest measles caseload globally [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Now, in eLife, Prabhat Jha of the University of Toronto and colleagues – including Benjamin Wong as first author – report how they were able to assess the full impact of this enormous immunization campaign (Wong et al, 2019). Wong et al used data from the Million Death Study, which systematically ascertains the cause of death in a nationally representative sample of deaths in India, including 27,000 child deaths from 1.3 million households between 2005 and 2013 (The Million Death Study Collaborators, 2010; Fadel et al, 2017; Gomes et al, 2017).…”
mentioning
confidence: 99%